2020
DOI: 10.1101/2020.03.01.971705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resting state fluctuations underlie free and creative verbal behaviors in the human brain

Abstract: Internally generated (free) ideas and creative thoughts constitute a fundamentally important aspect of the human experience, yet the neuronal mechanism driving these behaviors remains elusive. Here we examined the hypothesis that the common mechanism underlying free verbal behaviors is the ultra-slow activity fluctuations (termed "resting state fluctuations") that emerge spontaneously in the human brain.In our experiment, participants were asked to perform three voluntary verbal tasks: a verbal fluency task, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Interestingly, this finding is in line with our results demonstrating reduced creative fluency with DCS of left hemisphere DN and no change in originality, further suggesting a role for right hemisphere DN in original thinking. It should be noted that verbal and creative fluency are well correlated, and may partially overlap in function [34,35]. However, in all participating subjects, the cortex exposed during surgery was thoroughly mapped for language functions (stimulated systematically while evaluating for naming, comprehension, and free speech).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this finding is in line with our results demonstrating reduced creative fluency with DCS of left hemisphere DN and no change in originality, further suggesting a role for right hemisphere DN in original thinking. It should be noted that verbal and creative fluency are well correlated, and may partially overlap in function [34,35]. However, in all participating subjects, the cortex exposed during surgery was thoroughly mapped for language functions (stimulated systematically while evaluating for naming, comprehension, and free speech).…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in the introduction -numerous studies have revealed that these fluctuations are organized along highly complex but informative connectivity patterns (Fox et al, 2006;Fox & Raichle, 2007;Sadaghiani & Kleinschmidt, 2013;Strappini et al, 2019) suggested to be related to cognitive habits, traits and pathologies (Eldar et al, 2013;Hahamy et al, 2021;. Recently we have proposed (Broday-Dvir & Malach, 2021;Norman et al, 2017;Norman & Malach, 2022) that these spontaneous fluctuations constitute a universal driver of self-generated, voluntary and creative behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…They have also been linked to other spontaneous behavioral manifestations such as spontaneous fluctuations in pupil diameter (Yellin et al, 2015) and spontaneous eyedrifts (Ramot et al, 2011). Recently, we have demonstrated a direct link between the spontaneous activity fluctuations and free and creative verbal behaviors (Broday-Dvir & Malach, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…The hypothesis that APDs reflect the "switch into awareness" across different types of spontaneous behaviors is further evidenced by findings that conscious decisions, but not the actions that express those decisions, are accompanied by pupil dilations 27 . Notably, similar slow-ramping buildups of neural activity precede other types of spontaneous behavior, including creative idea generation 70 , eureka moments during problem solving 71 , and free recall 69,72 , which may reflect spontaneous fluctuations that trigger a thought or action upon crossing a threshold 39,42 . The similarities between volition and other spontaneous behavior are striking and, we think, deserve further exploration.…”
Section: Discussionmentioning
confidence: 99%